THE USE OF LOCAL IDENTITIES IN THE MONETARY PROPAGANDA OF THE POMPEIANS DURING THE WAR WITH CAESAR 49-48 BC - Kamil Kopij (Journal of Ancient History and Archaeology)
The issue of audience targeting is crucial in studies of contemporary propaganda. Meanwhile, it is usually ignored in analysis of Roman propaganda despite the fact that studies of ancient rhetoric clearly shows that speakers were well aware that they must use a different language when performing in front of different audiences. The primary aim of this paper is to consider the possibility of targeting propaganda messages encoded on coins struck by the Pompeians (RRC 444, RRC 445/1-3) during the war with Caesar. The analysis of the imagery placed on these coins may indicate that different types were in the first instance intended for the inhabitants of Epirus and Greece (RRC 444, RRC 445/2), Sicily (RRC 445/1) and West Asia Minor (RRC 445/3). Considering the fact that those were the most important areas of recruitment for the Pompeians, it is possible that by placing images that referred to them they tried to influence locals also in this way.